Ethanol fermentation by the thermotolerant yeast, Kluyveromyces marxianus TISTR5925, of extracted sap from old oil palm trunk - Murata, Yoshinori; Danjarean, Hatairat; Fujimoto, Kiyohiko; Kosugi, Akihiko; Arai, Takamitsu; Ibrahim, Wan Asma; Suliman, Othman; Hashim, Rokiah; Mori, Yutaka (AIMS Press, 2015)
Palm sap extracted from old oil palm trunks was previously found to contain sugar and nutrients (amino acids and vitamins). Some palm saps contain a low content of sugar due to differences in species or in plant physiology. Here we condensed palm sap with a low content of sugar using flat membrane filtration, then fermented the condensed palm sap at high temperature using the thermotolerant, high ethanol-producing yeast, Kluyveromyces marxianus. Ethanol production under non-optimum conditions was evaluated. Furthermore, the energy required to concentrate the palm sap, and the amount of energy that could be generated from the ethanol, was calculated. The condensation of sugar in sap from palm trunk required for economically viable ethanol production was evaluated.